Association between systemic iron status and β-cell function and insulin sensitivity in patients with newly diagnosed type 2 diabetes - Qin, Yao; Huang, Yiting; Li, Yuxiao; Qin, Lu; Wei, Qianying; Chen, Xin; Yang, Chuanhui; Zhang, Mei (Frontiers in Endocrinology, 2023)
Objective: Abnormal iron metabolism is related to the risk of diabetes, but the underlying mechanism of this association remains uncertain. This study was conducted to evaluate the contributions of systemic iron status to β-cell function and insulin sensitivity of patients with newly diagnosed T2DM. Methods: A total of 162 patients with newly diagnosed T2DM and 162 healthy controls were enrolled in the study. Basic characteristics, biochemical indicators, and iron metabolism biomarkers, including serum iron (SI), ferritin (SF), transferrin (Trf), and transferrin saturation (TS), were collected. All patients underwent a 75 g oral glucose tolerance test. A series of parameters for assessing β-cell function and insulin sensitivity were calculated. The multivariate stepwise linear regression model was used to investigate the contributions of iron metabolism to β-cell function and insulin sensitivity. Results: Compared with healthy controls, patients with newly diagnosed T2DM had significantly higher levels of SF. Among the diabetic patients, the SI and TS levels were higher, and the percentage of Trf levels below normal values was lower in men than in women. In all diabetic patients, SF was the independent risk factor associated with impaired β-cell function. Further stratification analysis showed that Trf was an independent protective factor for β-cell function in male patients, while SF was an independent risk factor for impaired β-cell function in female patients. However, systemic iron status did not affect insulin sensitivity. Conclusion: Elevated SF levels and decreased Trf levels had a profound effect on impaired β-cell function in Chinese patients with newly diagnosed T2DM.